2023
DOI: 10.1590/1413-785220233101e261132
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Epidemiology of Adhesive Capsulitis During the Covid-19 Pandemic

Abstract: Objective: To evaluate a possible increase of adhesive capsulitis incidence during the COVID-19 pandemic. Methods: A total of 1,983 patients with shoulder disorders were retrospectively analyzed regarding gender, age, development of adhesive capsulitis and comorbidities (systemic arterial hypertension, diabetes mellitus, dyslipidemia, hypothyroidism, hyperthyroidism, depression, and anxiety) in two different periods: from March 2019 to February 2020 and from March 2020 to February 2021. Descriptive and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…[ 18 ] A cross-sectional study found that the chance of developing FS in patients with Hypothyroidism was 2.69 times higher than that of the normal population [ 10 ] and this chance may increase to 5 times during the COVID-19 pandemic. [ 36 ] Kumar et al [ 37 ] proposed that diabetes and thyroid diseases are characterized by a pro-inflammatory state, elevated levels of inflammatory cytokines, and increased fibrosis, leading to an inflammatory response in the shoulder joint, promoting fibrosis in the muscles around the shoulder, and further increase the risk of developing FS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 ] A cross-sectional study found that the chance of developing FS in patients with Hypothyroidism was 2.69 times higher than that of the normal population [ 10 ] and this chance may increase to 5 times during the COVID-19 pandemic. [ 36 ] Kumar et al [ 37 ] proposed that diabetes and thyroid diseases are characterized by a pro-inflammatory state, elevated levels of inflammatory cytokines, and increased fibrosis, leading to an inflammatory response in the shoulder joint, promoting fibrosis in the muscles around the shoulder, and further increase the risk of developing FS.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have reported conflicting findings regarding this relationship. One study did not find a significant correlation between AIH and FS, [ 36 ] but another study suggested a 1.22 times higher risk of developing FS in AIH patients during a 7-year follow-up. [ 11 ] These discrepancies could be attributed to factors such as unmeasured confounders and variations in sample sizes among different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Mello et al, through a retrospective analysis of 1,983 patients with shoulder disorders during the COVID-19 pandemic, identified a 2.41-fold surge in AC cases compared to the preceding year. Notably, patients with anxiety exhibited a substantially heightened 14-fold risk of developing AC during the pandemic (30). In a prospective study, Toprak et AC and 72 healthy controls, examining anxiety, depression, sleep quality, and quality of life in patients with AC relative to controls.…”
Section: Discussionmentioning
confidence: 99%
“…[24] By retrospectively analyzing 1983 patients with frozen shoulder during the novel coronavirus epidemic, Mello et al found a significantly increased risk of 8.8-fold (P < .001) of developing frozen shoulder in depressed patients. [25] However, Floren et al prospectively included 77 patients who underwent arthroscopic rotator cuff repair. At 6-month follow-up, eight patients were diagnosed with frozen shoulder (group A) and 65 patients had a satisfactory range of motion of the joint (group B), and by comparing the 2 groups depression was found not to be a risk factor for the development of frozen shoulder after rotator cuff repair.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] By retrospectively analyzing 1983 patients with frozen shoulder during the novel coronavirus epidemic, Mello et al found a significantly increased risk of 8.8-fold ( P < .001) of developing frozen shoulder in depressed patients. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%